2010
DOI: 10.1093/ejechocard/jep223
|View full text |Cite
|
Sign up to set email alerts
|

Stress echocardiography in the district hospital setting: a cost-saving analysis

Abstract: Stress echocardiography is a cost saving method for the investigation of chest pain in patients with low-intermediate risk of flow limiting coronary artery disease in the district hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…CAD indicates coronary artery disease; cath, cardiac catheterization; ECHO, echocardiography; MI, myocardial infarction; MPI, myocardial perfusion imaging; NA, not available from article.*Jang et al, 35 Charvat et al, 39 and Hannoush et al 36 reported prior coronary artery bypass graft surgery only and did not report prior percutaneous coronary intervention.*Diamond et al 38 reported prevalence only in patients with normal exercise test result.*Wennike et al, 31 Charvat et al, 39 Koistinen et al, 25 and Roeters van Lennep et al 33 reported prevalence only in patients with abnormal exercise test result.…”
Section: Resultsmentioning
confidence: 99%
“…CAD indicates coronary artery disease; cath, cardiac catheterization; ECHO, echocardiography; MI, myocardial infarction; MPI, myocardial perfusion imaging; NA, not available from article.*Jang et al, 35 Charvat et al, 39 and Hannoush et al 36 reported prior coronary artery bypass graft surgery only and did not report prior percutaneous coronary intervention.*Diamond et al 38 reported prevalence only in patients with normal exercise test result.*Wennike et al, 31 Charvat et al, 39 Koistinen et al, 25 and Roeters van Lennep et al 33 reported prevalence only in patients with abnormal exercise test result.…”
Section: Resultsmentioning
confidence: 99%
“…The PTPs were not reported, or expressed as prevalence of CAD, in two publications [40,49]. A further study reported PTP as low to CCA n = 1 CCA [48] n = 1 CCA [40]* n = 0 n = 0 n= 0 n= 2 CCA [40,48] The cost-effectiveness of a screening strategy involving SPECT versus direct referral to ICA was evaluated in five studies with SPECT resulting to be costeffective in almost all these studies (four out of five) despite the different populations considered. SPECT was a cost-saving approach either in one study involving patients with high PTP (>85%) [25] and in a study involving patients with low PTP [37].…”
Section: Resultsmentioning
confidence: 94%
“…Two studies both undertaking a cost-consequence analysis were also found [40,48]. Of all CEAs, many were US based (9 of 31, 29%; see SUPPLEMENTARY TABLE S2) and a further 8 (26%) studies were UK based.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ever cost effectiveness is a major aspect of all work performed in the national health service and stress echocardiography has been shown to a very cost effective way of reducing the need for invasive angiography [15] and now it is clear that money saved is not likely to be wasted when there are late events in follow up.…”
Section: Discussionmentioning
confidence: 99%